Hematochezia in a Child With Heiner Syndrome - Liu, Xiang-Yu; Huang, Xi-Ru; Zhang, Jie-Wei; Xiao, Yong-Mei; Zhang, Ting (Frontiers in Pediatrics, 2020)
Heiner syndrome (HS) is a food hypersensitivity disease that is mostly caused by cow's milk. The main features may include chronic or recurrent respiratory syndromes, pulmonary infiltrates on radiography, and even pulmonary hemosiderosis. However, gastrointestinal symptoms are rare in HS, which can lead to a misdiagnosis when the chief complaint is about the gastrointestinal system. Here, we report a case of HS complicated by severe hematochezia.